Dialek Sebagai Identitas Masyarakat Bahasa di Pulau Lombok - Dedad Bisaraguna Akastangga, Muhammad (International Seminar on Austronesian Languages and Literature, 2021)
Language is a means of communication as well as the identity of a particular society. A language community is all people who use a particular language (dialect). On the island of Lombok, NTB, there are several dialects that are used by speakers of the language and at the same time become the identity of a community. This study tries to describe the identity of the people of Lombok NTB seen from the dialect aspect used. To describe the identity of the people on the island of Lombok, NTB, the researchers used descriptive qualitative research methods with a sociolinguistic approach. The data collection method used is the listening method with face-to-face conversational techniques, interviews, and note-taking techniques. The purpose of this study is to describe the dialects that exist on the island of Lombok NTB as an identity or characteristic of a particular community. Based on observations, it was found that several types of dialects are widely used on the island of Lombok as the identity of an area, namely: meno-mene dialect, ngeto-ngete dialect, ngeno-ngene dialect, and meriak-meriku dialect. All of these dialects make the area have the characteristics of a language-speaking community as well as become the identity of an area where the native speakers of that language live